Pengembangan Panduan Praktikum Elektronik Berbasis Green Chemistry Dengan Model Problem Based Learning Materi Ikatan Kimia - Riski Dwi Saputri; Nancy Willian; Yudi Umara (Departement of Mathematics Education, 2024)
The objectives of this research are 1) to find out the process of developing a green chemistry-based electronics practicum guide with a problem based learning model on chemical bonding material 2) to find out the validity of developing a green chemistry-based electronics practicum guide with a problem based learning model on chemical bonding material 3) to find out the practicality of developing a practicum guide green chemistry-based electronics with a problem based learning model regarding chemical bonds. This research is research into the R&D model of Hanaffin and Peck (needs analysis, design, development and implementation). This research involved class XI 3 students at SMAN 2 Tanjungpinang, while the sample was 40 students. The results of the research show that the development of the electronic practicum guide meets the valid criteria with material validation test results of 75.00% in the valid category. The results of the validation test for teaching materials were 75.00% valid criteria. The results of the test on the practicality of the teacher's response received a score of 87.50%, a very practical criterion, and the practicality of the student's response was 83.55%, a very practical criterion. Based on the research findings that have been carried out, it can be concluded that the green chemistry-based electronic practicum guide with a problem based learning model on chemical bonding material is valid and practical to use as teaching material.